Adaptation and validation of the brief sexual opinion survey (SOS) in a colombian sample and factorial equivalence with the Spanish version (2016)
Attitudes toward sexuality are a key variable for sexual health. It is really important for psychology and education to have adapted and validated questionnaires to evaluate these attitudes. Therefore, the objective of this research was to adapt, validate and calculate the equivalence of the Colombia Sexual Opinion Survey as compared to the same survey from Spain. To this end, a total of eight experts were consulted and 1,167 subjects from Colombia and Spain answered the Sexual Opinion Survey, the Sexual Assertiveness Scale, the Massachusetts General Hospital-Sexual Functioning Questionnaire, and the Sexuality Scale. The evaluation was conducted by online and the results show adequate qualitative and quantitative properties of the items, with adequate reliability and external validity and compliance with the strong invariance between the two countries. Consequently, the Colombia Sexual Opinion Survey is a valid and reliable scale and its scores can be compared with the ones from the Spain survey, with minimum bias. © 2016 Vallejo-Medina et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.